(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The present study sought to assess the effectiveness of a music-based teaching strategy for strengthening orality in preschool children at the Guamalito, Bajo Plumero site. A quasi-experimental design was used with a treatment group and a control group, and several activities were implemented to strengthen orality through music. A quasi-experimental design including a control group and a treatment group was used. The groups were selected from the preschool student population of the Guamalito, Bajo Plumero branch of the Arenoso Rural Educational Institution. The sample consisted of 20 preschool students. The main instruments used were an observation form and an evaluation grid for each activity. The results obtained showed a significant improvement in the orality of the students in the treatment group compared to the control group. Strengths and weaknesses in the implementation of the didactic strategy were identified, and adjustments and improvements were made for future implementations. It is concluded that the music-based didactic strategy is effective for strengthening orality in preschool children, and its implementation in other educational contexts is recommended. It is necessary to continue researching and improving didactic strategies for strengthening orality in early childhood.